The effectiveness of Bobath technique in treating children with cerebral palsy: a systematic review - Mohd Dar, Shahid; Johari, Nur Atiqah (International Islamic University Malaysia, 2024)
Aim: To assess how Bobath therapy affects motor function and functional independence. Method: This systematic review was conducted following PRISMA guidelines. All randomized control trials (RCTs) that recruited cerebral palsy children and applied the Bobath approach as an intervention were collected through a comprehensive online database search. For quality assessment, the revised Cochrane risk-of-bias tool for randomized trial (RoB 2) was used. Results: Six eligible articles including five RCTs and one quasiexperimental study were retrieved from PEDro, MEDLINE, COCHRANE, EBSCO and PubMed since 2010, and all studies had low risk of bias. The Bobath therapy had shown positive effects on gross motor function, balance, upper extremity function and functional independence with no significant effects on gait parameters and disability involvement. Conclusion: The Bobath technique would not be effective on its own but may give more advantages if it is used as an adjunct to other conventional physiotherapy treatments.